DENSITY AND GONAD MATURITY LEVEL OF MANGROVE SHELLS Polymesoda expansa PUTERI SEMBILAN ESTUARY RUPAT UTARA BENGKALIS REGENCY IN RIAU - Febrinal Syahputra; Yusni Ikhwan; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in July 2014, located at the Putri Sembilan estuary District of Rupat Utara. Mangrove clams P. expansa is one of the favorite seafood of Rupat Utara coastal communities. In addition as a side dish, clamshell are also used as a household accessories. This study aims to determine the density and maturity level gonad of mangrove clam P. expansa. The method used in this study is a survey method and determination of observation stations was determined by purposive sampling method, where the location of the study divided into three stations. The results showed that the density of higher mangrove clams P. expansa found at station II (± 100 meters from the mouth of the river upstream), while the lowest density was found at station I (outfall mouth of the river). The dominant gonad maturity level of mangrove clam P. expansa found was maturing stage (early stage) and least common was immature stage (period of gonadal development).Keywords: P. expansa, Density, Gonad Maturity Level, Rupat Island.